PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA GURU DAN PEGAWAI TATA USAHA MTs NEGERI NGAWI - Samsul Hadi (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2015)
Human Resources is a major asset in the organization. Humans become planners, implementers and active participants in all activities of the organization. Application of appropriate human resources in the organization will result in an increase in the ability of an organization to acquire and retain the best people in their fields. Performance evaluation and training will develop individual who requires skill, knowledge and attitudes different from what they have today. This study examines the leadership style is there any effect on the performance of teachers and administrative employees at MTs Negeri Ngawi. The study aims to determine the effect of leadership style on the performance of teachers and administrative employees at MTs Negeri Ngawi. From the results of the study found a correlation coefficient between leadership style and performance of teachers and administrative employees at MTs Negeri Ngawi at 0.681. This indicates that the style of leadership has positive influence on the performance of teachers and administrative employees. While the t-test results can be seen that the value of 7.623 t count is greater than the value that is equal to 3.229 ttable. So the null hypothesis is rejected and the hypothesis is accepted.